Outcomes of Emergency Groin Hernia Repair in the Elderly: A Systematic Review - Rodrigo Piltcher-da-Silva; Vivian Laís Sasaki; Luiz Francisco Cravo Bettini; Pedro San Martin Soares; Isabelle Garibaldi Valandro; Leandro Totti Cavazzola (Journal of Abdominal Wall Surgery)
Introduction: The number of surgeries for groin hernia (GH) among the elderly follows the increase in life expectancy of the population. The greater number and severity of comorbidities in this group increases the surgical risk, promoting discussion regarding the indication of elective surgery and the benefits of watchful waiting approach (WWA). The aim of the present study was to evaluate the outcomes of emergency hernia surgery among the elderly population.Materials and methods: A systematic review was performed in Pubmed and Scielo databases for the past early 10 years, until July 2022. The subject was groin hernia in the emergency setting focusing the elderly population. The PRISMA statement was followed and the classification of elderly was based on the World Health Organization’s definition.Results: A total of 1,037 results were returned and we ended with nine original articles with emphasis in groin hernia in the emergency among the elderly population. In these subjects, the complications rate ranged between 21.2% and 28.9% and the mortality rate ranged between 1.2% and 6%. Cardiopulmonary disease, high ASA and Charlson’s scales were associated with greater risk of complications and death.Conclusion: Emergency GH surgery in the elderly population carries an increased risk of complications and mortality. GH surgery is safe or, at least, less harmful when done electively. The risk and benefits of WWA and upfront surgery needs to be assessed and exposed to the patients. Our review sugest that elective surgery should be the option over WWA in this patient population.